Anxiolytic and Antistress Potentials of Ethanol Stem-Bark Extract of Milicia Excelsa (Moraceae) in Mice: Anxiolytic and Antistress Potentials of Milicia excelsa in mice - Aiyelero, Oyeronke Medinat; Adeyemi, Issac Oluwole; Akinpelu, Lateef Abiola; Akanmu, Moses Atanda (Iranian Journal of Pharmaceutical Sciences, 2023)
Milicia excelsa stem bark is applied in traditional medicine in some African societies, primarily as a tonic to rejuvenate the body after demanding episodes. However, there is a paucity of scientific evidence to support this usage. Therefore, this research aimed to evaluate the anxiolytic and anti-stress potentials of ethanol extract of the stem bark of Milicia excelsa (ESBME) in mice. The central nervous system inhibitory effect of the extract was determined using novelty-induced rearing, grooming, and locomotion behaviors while the anxiolytic effect was investigated by using a hole board and elevated plus maze (EPM) test models. The extract’s ability to alleviate the anxiety-like and depressive-like behaviors triggered by acute restraint stress was evaluated with the use of EPM and tail suspension test respectively. The ESBME significantly (p<0.05) decreased the novelty-induced rearing, grooming, and locomotion behaviors indicating a central nervous system inhibitory effect. At 37.5 mg/kg, ESBME significantly (p<0.05) increased the number of head poking in the hole board test designating anxiolytic potential. Subsequently, the ESBME significantly (p<0.05) increased the percentage of open-arm entries and percentage open-arm duration as well as reducing the anxiety index on elevated plus Maze consistent with the antianxiety effect. The extract also significantly (p<0.05) alleviated the anxiety-like and depressive-like behaviors triggered by acute restraint stress suggesting an anti-stress effect. In conclusion, ESBME possesses central nervous system inhibitory, anxiolytic, and anti-stress effects thereby providing scientific evidence to the ethnomedicinal claim of the plant as an anti-stress agent.